Evidence based review of literature on detriments to healing of diabetic foot ulcers. Issue 4 (December 2017) - Lefrancois, Tina; Mehta, Kinjal; Sullivan, Victoria; Lin, Sheldon; Glazebrook, Mark
Highlights: This paper provides a comprehensive review of literature on the detriments to healing of diabetic foot ulcers. This paper will assist in guiding physicians on effective treatment of diabetic foot ulcers. This paper will highlight areas of research potential for treatment of diabetic foot ulcers. Abstract: Background: Diabetes mellitus places a substantial burden on society worldwide. Diabetic foot ulcers are a challenging problem for clinicians. Seven generally accepted detriments to healing of diabetic foot ulcers were identified: infection, glycaemic control, vascular supply, smoking, nutrition, deformity and offloading. The aim of this paper is to present a comprehensive evidence based review of the literature available on detriments to healing of diabetic foot ulcers. Method: A research question was generated for each of the detriments to healing and a comprehensive review of the literature was performed using the Pubmed database in July 2014. All articles were assessed for relevancy and a level of evidence was assigned. An analysis of the total body of literature was used to assign a grade of recommendation to each detriment. Results: Grade A recommendation was assigned to offloading as there was good evidence supporting this intervention. Grade B recommendation was assigned to deformity as there was fair evidence consistent with the hypothesis. Infection and vascular supply had poor quality evidence supporting the research question and grade C recommendation was assigned. Grade I recommendation was assigned to glycaemic control, smoking and nutrition as there was insufficient and conflicting evidence available. Conclusion: Our literature review revealed good evidence for some factors and insufficient literature on others. Further studies are needed to provide quality evidence regarding detriments to healing of diabetic ulcers.